Towards an inductive design of distributed object oriented databases - Baido, F.; Mattoso, M.; Zaverucha, G. (3rd IFCIS International Conference on Cooperative Information Systems : proceedings, August 20-22, 1998, New York City, New York, USA, 1998)
Cooperative information systems (CIS) often consist of applications that access shared resources such as databases. Since centralized systems may have a great impact on the system performance, parallel and distribution techniques are needed for attaining scalability. Distributed databases are, then, crucial for the development of cooperative applications. However, in order to improve performance, it is very important to design information distribution properly, which is the goal of distribution design. Considering the various difficulties embedded in the design of distributed object oriented databases, this work presents an algorithm to assist distribution designers in their task. The analysis algorithm indicates the most adequate fragmentation technique (vertical, horizontal or mixed) for each class in the database schema, and we propose the use of a machine learning method-inductive logic programming-to uncover some implicit issues to be considered in the distribution design, thus revising the proposed analysis algorithm.